A Qualitative Market Analysis Applied to Mini-FLOTAC and Fill-FLOTAC for Diagnosis of Helminth Infections in Ruminants - Maurelli, Maria Paola; Dourado Martins, Oliva Maria; Morgan, Eric R.; Charlier, Johannes; Cringoli, Giuseppe; Mateus, Teresa Letra; Bacescu, Bogdan; Chartier, Christophe; Claerebout, Edwin; de Waal, Theo; Helm, Christina; Hertzberg, Hubertus; et al. (Frontiers in Veterinary Science, 2020)
Helminth infections, mainly by gastrointestinal nematodes (GIN), are one of the main concerns for animal health, welfare and productivity in grazing ruminant livestock worldwide. The use of a sensitive, precise, accurate, low-cost, and easy-to-perform copromicroscopic technique is of pivotal importance to perform reliable fecal egg count (FEC) and fecal egg count reduction test (FECRT), in order to determine the need of anthelmintic treatment, but also anthelmintic efficacy or resistance. This approach is fundamental to a correct and efficient control of GIN. Unfortunately, in worldwide ruminant farm practice, repeated anthelmintic treatments are carried out, without prior diagnosis of infection, contributing to the spread of Anthelmintic Resistance (AR). Tackling this phenomenon, improving mainly the GIN diagnosis and AR status in farm animals, is a priority of the European COST Action “COMBAR—COMBatting Anthelmintic Resistance in Ruminants” and of the STAR-IDAZ International Research Consortium on Animal Health. One of the specific objectives of the COMBAR Working Group 1 (WG1) is to conduct an European market analysis of new diagnostics and develop a business plan for commercial test introduction, leveraging technical know-how of participants. Since the Mini-FLOTAC in combination with the Fill-FLOTAC may be considered a good candidate for a standardized FEC and FECRT in the laboratory, as well as directly in the field, the aim of this study was to conduct SWOT (Strength—Weaknesses—Opportunities—Threats) and PESTEL (Political, Economic, Social, Technological, Environmental, and Legal) analyses of these tools in 20 European countries involved in the COMBAR WG1, in order to identify the opportunities, barriers, and challenges that might affect the Mini-FLOTAC and Fill-FLOTAC commercialization in Europe.